The central role of the cytoskeleton in mechanisms and functions of the NK cell immune synapse. Issue 1 (10th October 2013) - Lagrue, Kathryn; Carisey, Alex; Oszmiana, Anna; Kennedy, Philippa R.; Williamson, David J.; Cartwright, Adam; Barthen, Charlotte; Davis, Daniel M.
Summary: Natural killer (NK) cells discriminate between healthy and unhealthy target cells through a balance of activating and inhibitory signals at direct intercellular contacts called immune synapses. Rearrangements in the cellular cytoskeleton have long been known to be critical in assembly of immune synapses. Here, through bringing together the vast literature on this subject, the number of different ways in which the cytoskeleton is important becomes evident. The dynamics of filamentous actin are critical in (i) creating the nanometer‐scale organization of NK cell receptors, (ii) establishing cellular polarity, (iii) coordinating immune receptor and integrin‐mediated signaling, and (iv) directing secretion of lytic granules and cytokines. The microtubule network also is important in the delivery of lytic granules and vesicles containing cytokines to the immune synapse. Together, these data establish that the cytoskeleton acts as a central regulator of this complex and dynamic process – and an enormous amount of NK cell biology is controlled through the cytoskeleton.